High-Dose Ceftriaxone in Elderly Patients with Enterococcal Infective Endocarditis: Population Pharmacokinetics of Free Ceftriaxone and Dose Optimization - Beatriz Fernández Rubio; Fernando Docobo Pérez; Laura Herrera Hidalgo; Luis Eduardo López-Cortés; Rafael Luque Márquez; José Manuel Lomas Cabezas; Luis Fernando López-Cortés; Marta Mejías Trueba; Ana Belén Guisado Gil; Alicia Gutiérrez Valencia; Arístides de Alarcón González; María Victoria Gil Navarro (Antibiotics)
Background: Ampicillin plus ceftriaxone (AC) is a first-line treatment for Enterococcus faecalis infective endocarditis (IE). Its administration in outpatient parenteral antibiotic treatment (OPAT) programs is challenging. The design of a ceftriaxone regimen suitable for OPAT requires deep knowledge of ceftriaxone pharmacokinetics (PK). Objective: We aim to explore ceftriaxone PK in elderly patients and propose dose regimens adapted to OPAT to maintain synergistic concentrations (Cs) with ampicillin against E. faecalis. Methods: We conducted a prospective observational pharmacokinetic study on patients (>55 years old) affected by E. faecalis IE. Ceftriaxone free concentration was measured at three time-points: before the administration (Cmin) and two and four hours after ceftriaxone administration (C2 and C4). Both structural and covariate population pharmacokinetic models were built. Monte Carlo simulations of six ceftriaxone dosages were performed and the probability of target attainment (PTA) of an optimal Cs range was analyzed. The pharmacokinetic/pharmacodynamic index (PK/PD) to predict efficacy was defined as maintaining free ceftriaxone concentrations superior to the Cs at 50–100% of the dosing interval (fT ≥ Cs ≥ 50–100% of the dosing interval). Ceftriaxone dosing regimens were considered optimal if at least 90% of the simulated population was able to achieve the defined PK/PD targets. Results: Twenty-four episodes from 16 patients were included. Mean free ceftriaxone concentration pre-dose, +2 h, and +4 h were Cmin = 7.8 ± 6.5 mg/L, C2 = 34 ± 26.5 mg/L, and C4 = 22.7 ± 19.7 mg/L, respectively. A two-compartment model with first-order absorption and elimination best described the data. Ceftriaxone one-hour infusions only achieved the minimum PK/PD target when the 2 g/12 h regimen was tested. On the other hand, ceftriaxone continuous infusion maintained a Cs above the PK/PD target for 100% of the dosing interval using ceftriaxone 4–6 g regimens. Conclusions: Our findings suggest that the optimal ceftriaxone exposure may be achieved using high-dose continuous infusions to ensure an ampicillin-killing effect when treating E. faecalis IE.